The deep evolution of metazoan microRNAs - Wheeler, Benjamin M.; Holstein, Thomas W. (Evolution & development, 2009)
SUMMARY microRNAs (miRNAs) are approximately 22-nucleotide noncoding RNA regulatory genes that are key players in cellular differentiation and homeostasis. They might also play important roles in shaping metazoan macroevolution. Previous studies have shown that miRNAs are continuously being added to metazoan genomes through time, and, once integrated into gene regulatory networks, show only rare mutations within the primary sequence of the mature gene product and are only rarely secondarily lost. However, because the conclusions from these studies were largely based on phylogenetic conservation of miRNAs between model systems like Drosophila and the taxon of interest, it was unclear if these trends would describe most miRNAs in most metazoan taxa. Here, we describe the shared complement of miRNAs among 18 animal species using a combination of 454 sequencing of small RNA libraries with genomic searches. We show that the evolutionary trends elucidated from the model systems are generally true for all miRNA families and metazoan taxa explored: the continuous addition of miRNA families with only rare substitutions to the mature sequence, and only rare instances of secondary loss. Despite this conservation, we document evolutionary stable shifts to the determination of position 1 of the mature sequence, a phenomenon we call seed shifting, as well as the ability to post-transcriptionally edit the 5′ end of the mature read, changing the identity of the seed sequence and possibly the repertoire of downstream targets. Finally, we describe a novel type of miRNA in demosponges that, although shows a different pre-miRNA structure, still shows remarkable conservation of the mature sequence in the two sponge species analyzed. We propose that miRNAs might be excellent phylogenetic markers, and suggest that the advent of morphological complexity might have its roots in miRNA innovation.